2012
DOI: 10.1038/nsmb.2357
|View full text |Cite
|
Sign up to set email alerts
|

RNA cytosine methylation by Dnmt2 and NSun2 promotes tRNA stability and protein synthesis

Abstract: The function of cytosine-C5 methylation, a widespread modification of tRNAs, has remained obscure, particularly in mammals. We have now developed a mouse strain defective in cytosine-C5 tRNA methylation, by disrupting both the Dnmt2 and the NSun2 tRNA methyltransferases. Although the lack of either enzyme alone has no detectable effects on mouse viability, double mutants showed a synthetic lethal interaction, with an underdeveloped phenotype and impaired cellular differentiation. tRNA methylation analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
527
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 499 publications
(560 citation statements)
references
References 37 publications
19
527
1
2
Order By: Relevance
“…Defects of tRNA modifications might cause tRNA degradation, resulting in decreased translation efficiency, increased translational errors, and altered cellular metabolism and signaling pathways (Chen et al, 2010;Tuorto et al, 2012). Thus, tRNA methylation changes could provide a possible mechanistic explanation for the defects observed in mat3.…”
Section: Discussionmentioning
confidence: 99%
“…Defects of tRNA modifications might cause tRNA degradation, resulting in decreased translation efficiency, increased translational errors, and altered cellular metabolism and signaling pathways (Chen et al, 2010;Tuorto et al, 2012). Thus, tRNA methylation changes could provide a possible mechanistic explanation for the defects observed in mat3.…”
Section: Discussionmentioning
confidence: 99%
“…m 5 C modifications can be installed by any of the seven proteins of the Nol1/Nop2/SUN domain (NSUN) family and by an enzyme named DNA methyltransferase 2 (DNMT2). DNMT2 mainly catalyses the m 5 C modification in position 38 of tRNA Asp in human cells (Goll et al , 2006), while the so far characterised NSUN proteins show specificity for tRNAs (NSUN2, NSUN6; Schaefer et al , 2010; Tuorto et al , 2012; Blanco et al , 2014; Haag et al , 2015a) or rRNA (NSUN1/NOP2, NSUN5; Sloan et al , 2013; Tafforeau et al , 2013; Schosserer et al , 2015). NSUN2 can also modify vault RNAs and mRNAs (Hussain et al , 2013), and NSUN4 was described to localise to mitochondria where it was shown to methylate the mitochondrial 12S rRNA in mice (Cámara et al , 2011; Metodiev et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…RNA modifications are particularly enriched in tRNAs, where they are often linked to translational regulation (Agris 2008). In this context, it has been shown that m5C modification of tRNA plays an important role in tRNA stability and in the regulation of translational fidelity (Schaefer et al 2010;Tuorto et al 2012Tuorto et al , 2015. Furthermore, m5C is also a widely conserved modification of rRNA, where it is implied in the quality control of ribosome biogenesis (Sharma et al 2013;Bourgeois et al 2015;Schosserer et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%